The Implementation of the Kyoto Protocol and the impact of national laws and policies of sustainable development: Analysis on the Malaysian situation - Asril Amirul, Zakariah (2013)
The Kyoto Protocol’s commitment period ended at the end of 2012. The literature discussing the implementation of the Kyoto Protocol in developing countries such as Malaysia is rare and limited. This is due to the fact that the Protocol only requires commitments from developed countries in order to reach its objective. The only relevant provisions to be discussed under the Protocol relevant to developing nations such as Malaysia are article 10 and 12, the former being the general obligations of Parties to the Protocol and the latter the Clean Development Mechanism (CDM). The purpose of this paper is to evaluate and analyze the Malaysian national implementation of the Kyoto Protocol of the United Nations Framework Convention on Climate Change (UNFCCC) and ‘green’ developments such as the CDM and the latest feed-in-tariff system implemented in Malaysia. Various national policies and laws such as the National Renewable Energy Policy and Action Plan 2009 and the Renewable Energy Act 2011 will be looked into to ascertain whether such policies and laws do support the spirit and purpose of the Convention. Analysis is also conducted on the current list of all relevant Malaysian CDM projects. With the findings, recommendations are made, especially on the legal perspective in order to make the Malaysian national implementation better so that the ultimate objective of the Convention can be achieved.